Medium optimization and structural characterization of exopolysaccharides from endophytic bacterium Paenibacillus polymyxa EJS-3 - Liu, Jun; Luo, Jianguang; Ye, Hong; Sun, Yi; Lu, Zhaoxin; Zeng, Xiaoxiong (Carbohydrate polymers, 2010)
In this study, response surface methodology was employed to optimize the medium compositions for the production of exopolysaccharides (EPS) from endophytic bacterium Paenibacillus polymyxa EJS-3. Firstly, fractional factorial design was applied to evaluate the effects of different components in the medium. It was found that sucrose, yeast extract and CaCl 2 influenced significantly the production of EPS. Then, steepest ascent method and central composite design were used to optimize the concentrations of the three variables. As results, the optimal medium compositions were determined as following (g/L): sucrose 188.2, yeast extract 25.8, K 2HPO 4 5 and CaCl 2 0.34, with a corresponding yield of 35.26 g/L. In addition, both polysaccharide fractions (EPS-1 and EPS-2) from crude EPS were mainly composed of (2 → 6)-linked β- d-fructofuranosyl residues backbone with (2 → 1)-linked branches based on their structural characterization by FT-IR spectroscopy, methylation analysis and 13C NMR spectroscopy.